Against the Market / Political Economy, Market Socialism and the Marxist Critique - Mcnally David (Verso, 1993)
A powerful critique of market socialism, by tracing it back to its roots in early political economy. Preface, Introduction, Origins of Capitalism and the Market, Justice and Markets: The Ambiguous Legacy of Adam Smith, The Malthusian Moment: Political Economy versus Popular Radicalism, Exploitation and Inequality and the Market: The Making of Popular Political Economy, ''Proudhon Did Enormous Mischief'': Marx's Critique of the First Market Socialists, Beyond the Market, Conclusion, Notes, Index.